Pragmatism and Experimental Bioethics - Rydenfelt, Henrik 1982- (2024)
Pragmatism gained considerable attention in bioethical discussions in the early 21st century. However, some dimensions and contributions of pragmatism to bioethics remain underexplored in both research and practice. It is argued that pragmatism can make a distinctive contribution to bioethics through its concept, developed by Charles S. Peirce and John Dewey, that ethical issues can be resolved through experimental inquiry. Dewey’s proposal that policies can be confirmed or disconfirmed through experimentation is developed by comparing it to the confirmation of scientific hypotheses, with a focus on the objection that the consequences of following a moral view or policy do not provide guidance on choosing among competing ethical perspectives. As confirmation of scientific hypotheses typically relies on evidence gathered from observation, the possibility of ethically relevant observation is then explored based on Peirce’s views on feelings as emotional interpretants. Finally, the connection between Dewey’s experimental ethics and democracy is outlined and compared to unfettered ethical progressivism.
Keywords: Pragmatism; Confirmation; experimental ethics; Moral Progress; Observation